Bimuria omanensis sp. nov. (Didymosphaeriaceae, Pleosporales) from Oman - Wijesinghe, Subodini N.; Wanasinghe, Dhanushka N.; Maharachchikumbura, Sajeewa S. N.; Wang, Yong; Al-Sadi, Abdullah M.; Hyde, Kevin D. (Phytotaxa, 2020)
Bimuria is a monotypic genus in Didymosphaeriaceae, typified by B. novae-zelandiae collected in terrestrial habitats from New Zealand soil. In our study, Bimuria omanensis, a novel species was isolated from unidentified decaying leaves in Oman. The phylogenetic placement of B. omanensis is resolved based on maximum likelihood, maximum parsimony and Bayesian analyses of combined LSU, ITS and TEF1-α sequence data of Didymosphaeriaceae. The placement of Bimuria omanensis as a distinct species, is confirmed based on phylogeny. This is the first record of an asexual morph in Bimuria and first record of a Bimuria species from Oman. The relationship of this taxon with other phylogenetically closely related Didymosphaeriaceae species is shown.